Chemical and structural nature of tribo-surface of aluminium-SiC composites at nanometre and micrometre length scales - Shorowordi, Kazi Md; Haseeb, A.S. Md. Abdul; Celis, Jean Pierre (Elsevier, 2006)
The worn surface of Al-SiC metal matrix composites (MMC) sliding against phenolic brake pad at a linear sliding speed of 1.62 m s(-1) under contact pressures of 0.75-3.00 MPa in a pin-on-disc apparatus was investigated. XPS was used to extract information from the top few nanometres of the worn surface, while scanning electron microscopy and energy dispersive X-ray microanalysis (SEM-EDX) provided information from within a few micrometres. Results reveal that the surface of Al-SiC undergoes significant chemical and physical changes during wear. The tribo-surface on Al-SiC is converted into a mixture that contains the constituents of Al-SiC and the phenolic pad counter body as well as oxygen from atmosphere. The worn surface obtained in the present study is suggested to consist of a relatively finely mixed top layer of a few mu m in thickness. The topmost few nanometres of this finely mixed layer is totally oxidized. In addition to the continuous top layer, a thick mechanically mixed layer (MML) termed as massive MML also forms. Its thickness and coverage is found to be load dependent. The massive MML is found to be stratified at places; it contains defects and is rather heterogeneous at the micrometre scale. The characteristics of the modified surface are discussed and a schematic model for the MML is proposed. (c) 2006 Elsevier B.V. All rights reserved.